Inductively coupled plasma reactive ion etching of CoFeB magnetic thin films in a CH3COOH/Ar gas mixture - Garay, Adrian Adalberto; Hwang, Su Min; Choi, Ji Hyun; Min, Byoung Chul; Chung, Chee Won (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The etch characteristics of TIN hard mask patterned CoFeB thin films were investigated using an inductively coupled plasma reactive ion etching in a CH3COOH/Ar gas mixture. The etch characteristics of CoFeB magnetic thin film and TiN hard masks were investigated as a function of gas mixture concentration, coil rf power, dc-bias voltage and gas pressure. As CH3COOH concentration in the CH3COOH/Ar gas mixture increased, the etch rates of CoFeB films and degree of anisotropy in the etch profile decreased, while increased coil rf-power and dc bias voltage and reduced gas pressure increased the etch rate and improved the etch profile. Additionally, a thick hydrocarbon layer was formed on the film surface at a dc-bias voltage of 100 V. X-ray photoelectron spectroscopy and optical emission spectroscopy analyses of the etched films at various CH3COOH concentrations suggest that CoFeB thin films etched in a CH3COOH/Ar gas mixture follow a physical sputtering etch mechanism assisted by oxidation of the film and formation of a protective inhibition layer on the film surface. Etching of TiN patterned CoFeB films with a high degree of anisotropy was accomplished without redepositions or etch residues when conducted under high sputtering conditions. (C) 2015 Elsevier Ltd. All rights reserved.